Legal Basis of State Support for Creating Innovative Medicinal Products - S. V. Vasyliev (Law and Safety)
The study is focused on the legal regulation of state support for the creation of innovative medicinal products. Establishment of the measures of state support for scientific research for creating innovative medicinal products within legislative acts and by-laws should help to increase the competitiveness of the pharmaceutical industry in Ukraine.